General principles relied on by the scholars towards modern developments: An analytical study. - Husni, Ahmad Muhammad (JESOC, 2020)
This research deals with the general principles on jurisprudence of developments, through which we can reach to the provisions of all the emerging issues. The problem of not referring to the knowledge of the provisions of these developments to the origin of each updated issue, but mostly just mentioning the emerging issue with its modern terminologies is what makes it difficult for people to understand and know the rule of the issue; Some of these principles are agreed upon such as the Holy Qur’an and Sunnah, whereas some are not agreed upon such as Istishab and Istihsan etc. This study focuses on how to refer to these principles for the sake of ijtihad on new developments, because the ijtihad that is complete and has the necessary available conditions and moves to manage the issue sought to find its provisions can then search the suitable Shariah provision by referring to the original evidence (the Holy Qur’an and Sunnah), and evidence of dependency such as Ijma’i (Consensus), Qiyas (analogy), al-urf (custom) and a’dah. The researcher will try to focus on the aspects of response to these principles to know the provisions of the new developments. The research adopts inductive approach to try to gather religious texts, views and fatwas on the issue by focusing on the ancient books of Islamic jurisprudence by following the four Imams and arranging their views, and then mentions the views of the contemporary jurists on the new emerging issue and their preference on the issue. The study reached to a number of results, the most important of which the scholars explained and divided them based on essential, complementary and embellishments because of their importance in deducing provisions especially in contemporary emerging issues by making analogy and explanation where there is lack of explicit evidence on the emerging issue.